2019
DOI: 10.1152/jn.00845.2018
|View full text |Cite
|
Sign up to set email alerts
|

Sustained envelope periodicity representations are associated with speech-in-noise performance in difficult listening conditions for younger and older adults

Abstract: Temporal modulations are an important part of speech signals. An accurate perception of these time-varying qualities of sound is necessary for successful communication. The current study investigates the relationship between sustained envelope encoding and speech-in-noise perception in a cohort of normal-hearing younger (ages 18–30 yr, n = 22) and older adults (ages 55–90+ yr, n = 35) using the subcortical auditory steady-state response (ASSR). ASSRs were measured in response to the envelope of 400-ms amplitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 66 publications
(116 reference statements)
3
10
0
Order By: Relevance
“…It may be surprising that SNR loss did not relate to age-group. However, this is consistent with other studies examining QuickSIN performance among groups of older listeners that are high-functioning and have limited hearing loss (e.g., McClaskey et al, 2019 ; Sheft et al, 2012 ). More interesting is the lack of a relationship between SNR loss and ITD digit segregation, which may suggest that the subtle individual differences in speech-in-noise identification among normal hearing younger and older listeners as measured by QuickSIN are not sensitive enough to account for variability in ITD digit segregation.…”
Section: Discussionsupporting
confidence: 91%
“…It may be surprising that SNR loss did not relate to age-group. However, this is consistent with other studies examining QuickSIN performance among groups of older listeners that are high-functioning and have limited hearing loss (e.g., McClaskey et al, 2019 ; Sheft et al, 2012 ). More interesting is the lack of a relationship between SNR loss and ITD digit segregation, which may suggest that the subtle individual differences in speech-in-noise identification among normal hearing younger and older listeners as measured by QuickSIN are not sensitive enough to account for variability in ITD digit segregation.…”
Section: Discussionsupporting
confidence: 91%
“…A less temporally distinct ascending acoustic code is thought to engage top-down cognitive resources by generating predictions to support decoding of modulated speech-like signals (Peelle & Wingfield, 2016;Pichora-Fuller et al, 2017;Caspary & Llano, 2018;Recanzone, 2018). Consistent with human and animal studies, the present study finds that weakening periodicity cues by decreasing modulation depth (SAM∆100% to SAM∆25%) decreased the percentage of neurons showing temporal phaselocking to the SAM envelope (Pichora-Fuller et al, 2007;Malone et al, 2010;Parthasarathy & Bartlett, 2011;Mamo et al, 2016;Kommajosyula et al, 2019;McClaskey et al, 2019). Previously we found that jittering the SAM envelope with a 1.0kHZ centered noise produced similar levels of repetition-enhancement to the SAM∆25% used in the present study (Kommajosyula et al, 2019).)…”
Section: Discussionsupporting
confidence: 86%
“…Alternatively, there is a possibility that cochlear gain loss reduced the EFR and that this behavior was not captured by the current version of the model for this type of stimulus. There is evidence that ageing degrades the ABR EFR (Fernandez et al, 2015;Keshishzadeh et al, 2020), although not every study finds an effect of age on the EFR (McClaskey et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, there is a possibility that cochlear gain loss reduced the EFR and that this behavior was not captured by the current version of the model for this type of stimulus. There is evidence that ageing degrades the ABR EFR (Fernandez et al, 2015; Keshishzadeh et al, 2020), although not every study finds an effect of age on the EFR (McClaskey et al, 2019). Additionally, recent invasive studies in mice have shown that, although ageing leads to a reduction of the sustained phase locked response at the level of spiral ganglion neurons, this effect is partially neutered by a compensatory gain mechanism effective in the IC (Parthasarathy et al, 2019).…”
Section: Discussionmentioning
confidence: 99%